Lugar no mundo: uma exploração dos espaços domésticos nos cinemas de Kleber Mendonça Filho e André Novais - Costa, Rodrigo Gadelha (2024)
This text deals with the research work carried out on the constitution of houses in the productions of Brazilian filmmakers Kleber Mendonça Filho and André Novais. It looks at the constitution of domestic environments in these works through the analysis of filmic spaces driven by comparisons between works. This research seeks to understand the spatial treatment given by the directors to the houses in their films, investigating how the procedures adopted to shape the filmic space are associated with the narrative and symbolic meanings attributed to certain elements such as objects, rooms and gestures linked to the house. The efforts made here are aimed at observing the insurgency of a recent Brazilian cinema that makes the house the main articulating space of its movements. The contributions of film theorists such as Ismail Xavier, Jacques Aumont and André Gardies, researchers in the field of architecture such as Benoît Goetz, Joseph Rykwert and Juhani Pallasmaa, as well as authors from the fields of philosophy, sociology and anthropology were essential to the construction of a theoretical and methodological framework around the house and space as problems related to cinema. The choice of these films was based on the assessment that these would be the works in which the directors most clearly place domestic spatialities as central elements both in their content and in their discourse. The feature films Som ao Redor (2012), Aquarius (2016) by Kleber Mendonça Filho and Ela volta na Quinta (2014) and Temporada (2018) were examined with greater emphasis. However, it is important to point out that other works by the directors were constantly revisited in order to observe the productions within a process of approximations and distances between the filmic spaces constituted between the works of the two directors. The research revealed that Kleber Mendonça Filho and André Novais Oliveira have different approaches to the representation of domestic space in their films. While Kleber makes the house a dynamic and central element in the narrative, André focuses on intimacy and the poetics of everyday life. Both explore the permeability of spaces, but their unique visions of the cinematic experience and the relationship between space and narrative are reflected in different ways. These differences contribute to the diversity of Brazilian cinema, demonstrating how each director constitutes a unique look at the domestic space.